Recent Progress in Developing Monolithic Perovskite/Si Tandem Solar Cells - Liu, Na; Wang, Lina; Xu, Fan; Wu, Jiafeng; Song, Tinglu; Chen, Qi (Frontiers in Chemistry, 2020)
Monolithic perovskite/Silicon tandem solar cells have reached a certified efficiency of 29. 1% in recent years. In this review, we discuss material design for monolithic perovskite/Si tandem solar cells, with the focus on the top-cell development to improve their performance. Firstly, we introduce different types of transparent electrodes with high transmittance and low sheet-resistance used in tandem solar cells. We then discuss the development of the wide-bandgap perovskite absorber for top-cells, especially the strategies to obtain the perovskite layers with good efficiency and stability. In addition, as a special functional layer in tandem solar cells, the recombination layers play an important role in device performance, wherein different configurations are summarized. Furthermore, tandem device cost analysis is discussed. This review summarizes the progress of monolithic perovskite/Silicon tandem solar cells in a pragmatic perspective, which may promote the commercialization of this technology.